High capacitance and energy density supercapacitor based on biomass-derived activated carbons with reduced graphene oxide binder. (June 2018) - Choi, Ji-Hyuk; Lee, Chongmin; Cho, Sungwhan; Moon, Geon Dae; kim, Byung-su; Chang, Hankwon; Jang, Hee Dong
Abstract: Reduced graphene oxide (RGO) is employed as a conductive binder for the unprecedentedly high performance of the used coffee grounds-derived AC (cAC) supercapacitor. The 2 wt% of RGO sheets in the cAC based electrode (cAC-2) successfully preserves high specific surface area of cAC and supports conductive networks decorated with oxygen groups, which synergistically improve charge storage capability. Furthermore, the wettability of the cAC-2 electrode enhanced by hydrophilic oxygen groups of RGO allows the easy access of the electrolyte to the pores of the electrode. The symmetric two electrode system exhibits outstanding charge storage capacity, reaching a high specific capacitance of 512 F g −1 in KOH electrolyte at 0.5 A g −1 which is nearly four times higher than that of cAC electrode with PVDF binders. Remarkable electrochemical performance is further demonstrated in EMIMTFSI electrolyte, including high specific capacitance of 440 F g −1 at 0.5 A g -1, with an excellent rate performance of 81.4% from 0.5 to 10 A g -1 . The record high energy density of 187.3 Wh kg −1 is achieved at a power density of 438 W kg −1 and maintains an energy density of 153.8 Wh kg −1 at 8750 W kg −1 in EMIMTFSI electrolyte. Graphical abstract: Novel-green electrode composed of biomass-derived activated carbons and RGO sheets as a binder was fabricated for ultrahigh performance supercapacitors. Image 1